KAJIAN HIDROLIS PENURUNAN ELEVASI DASAR SUNGAI TERHADAP BENDUNG KARET JATIMLEREK KABUPATEN JOMBANG - Suhudi Suhudi (BUANA SAINS, 2008)
Rubber Dam of Jatimlerek the including River Brantas of region middle, having wide 160 m divided 6 hole equipped that apron floor its down stream with length 12 m made of concrete. Problems that happened are well not balanced of bad material of river effect of barrage where bad material supply of river of upstream dam a little. As well as following with activity mining of sand. Impact that emerges is happened degradation of river bed especially at down stream apron floor, so that can lengthen hydraulic jump and impact scouring in down stream dam. Aim of this research is to get picture how far influence of degradation of river bed to the rubber dam which evaluated from facet of hydraulic. Result of analysis indicate that device floods control 100 year equal to 893,201 m3/s impact of hydraulic jump able to have an effect on to bad material stability river. Tractate force that happened exceed which is permitted causing movement of bad material of river and shown with existence of scouring bad of river in down stream dam in 1,97 m. Scouring river bed is also proved with analysis transportation of sediment that is KB 84 < KB 84-100 < KB 84-200. Scouring bad of river that happened continuously can influence stability dam and can generate damage (collapse) at apron floor dam